ANTIDIABETES ACTIVITY AND SENSORY OF TAPAK DARA LEAF TEA (Catharanthus roseus L.) IN VARIOUS TYPES OF SWEETENERS - Saputri, Gian Melinda; Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma (Universitas Trilogi, 2025)
Tapak Dara Leaf (Catharanthus roseus L.) is a traditional herbal plant known for its alkaloid and flavonoid content which are included in its phenolic compounds that offer various health benefits such as antidiabetic. Antidiabetic is related to its activity as an anti-α-amylase and antioxidant. Its application in medicine can be consumed in the form of tea drinks. The purpose of this study was to study the effect of various types of sweeteners on the activity as an antidiabetic and sensory of Tapak Dara Leaf (Catharanthus roseus L.) drinks. The design of this study used a Completely Randomized Design with one factor, namely 4 types of sucrose sweeteners, kelulut honey, commercial honey, and stevia and 1 unsweetened control, so that there were 5 treatments and 5 replications were carried out to obtain 25 experimental units. The parameters observed in this study included Physicochemical Tests and Organoleptic Tests. The results of the physicochemical test data were analyzed using analysis of variance. The analysis was continued if there was a significant effect with a further BNJ 5% test. Sensory test data were analyzed using Kruskal Wallis to determine the effect of treatment on the sensory characteristics tested. The results of this study indicate that the types of sweeteners used, namely sucrose, stingless bee honey, commercial honey, and stevia, have an effect on the antidiabetic activity and sensory of tapak dara leaf tea drinks. Tapak Dara Leaf Drink (Catharanthus roseus L.) with benefits as an antioxidant can be consumed by adding stingless bee honey as a sweetener, while as an anti-α-amylase with commercial honey as a sweetener.